PENGGUNAAN PENDEKATAN KONTRUKTIVIS DALAM PEMBELAJARAN IPA TENTANG KONSEP SIFAT DAN PERUBAHAN WUJUD BENDA DI KELAS IV SDN ARGASARI KECAMATAN KERTASARI KABUPATEN BANDUNG - Roni Hamdani, Acep; Meilani Emaningrum, Dwi (STKIP Subang, 2016)
This study was conducted based on the background of the lack of understanding of fourth grade students of SDN Argasari about the concept of nature and changes in states of matter. Then students better understand where the subject matter delivered by his own neighbor. This study aims to determine the learning outcome using constructivist approach. The population of this study were students at SDN Argasari Bandung regency, namely grade IV with a number of students as many as 30 people. The method used in this research is a classroom action research (Class Action Research). The research instrument used is a research instrument used in conducting the study investigators at the time was observai sheet, sheet guidance interviews, field notes, worksheets and test questions. From the results of student learning outcomes as follows: 1) the average value of: a) prior to the action 57.7; b) the first cycle of 81; and c) the second cycle of 93: 2) percentage of mastery learning: a) prior to the action of 46.7%; b) the first cycle of 83.3%; and c) the second cycle of 100 Application of the constructivist learning approach was found to increase student learning, with students actively involved with activities to identify, understand, interpret and solve problems.